Observing development of the young child - BEATY, Janice J. (Ohio : Merril Prentice Hall, 2002)
The book presents a unique system for observing and recording development of children ages 3 to 5 in early childhood classroom settings. It is based on a progression of children's skill development in six major areas. The text is designed for use by college students preparing to be teachers in prekindergarten programs ... The text focuses on six major aspects of child development: emotional. social, physical, cognitive, language, and creative.
Includes bibliography and index
Includes bibliographical references and index